2018
DOI: 10.1111/eip.12749
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism dysregulation at the onset of mental illness is not limited to first episode psychosis: A systematic review and meta‐analysis

Abstract: Aim: To compare the differences of glucose metabolism outcomes between treatment-naïve, patients with first episode psychosis (FEP) and mood disorders.Methods: We conducted a systematic review and meta-analysis of glucose intolerance in treatment-naïve, first episode patients with severe mental illnesses (SMIs). Results:We identified 31 eligible studies. Compared to healthy controls, FEP group have higher insulin and insulin resistance levels, and both groups have higher glucose tolerance test results.No signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 77 publications
(203 reference statements)
4
19
0
Order By: Relevance
“…Our results are consistent with previous research showing that the frequency of type 2 diabetes is two-fold higher in people with severe mental illness that in the general population [3,4,42]. Although fetal birth dimensions, socioeconomic factors, and lifestyle have been associated with both, severe mental illness and diabetes, later adjustment for mothersage, fatherssocioeconomic position, BMI and cognitive performance at conscription only explained a minor part of this association in our cohort.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with previous research showing that the frequency of type 2 diabetes is two-fold higher in people with severe mental illness that in the general population [3,4,42]. Although fetal birth dimensions, socioeconomic factors, and lifestyle have been associated with both, severe mental illness and diabetes, later adjustment for mothersage, fatherssocioeconomic position, BMI and cognitive performance at conscription only explained a minor part of this association in our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Birth weight was recorded in 100 g groups and analyzed in three categories: 2500 low birth weight; 2500-4000 normal birth weight; and !4000 g high birth weight. Ponderal index, calculated as birth weight [Kg]/birth length [meters] 3 , was also included as it is theoretically assumed to measure fetal growth and thereby discriminate between intra-uterine well-fed (high ponderal index) and disproportionate growth restricted newborns (low ponderal index) [40]. Ponderal index was analyzed as threecategory variable (1 st quintile; 2 nd -4 th quintile; 5th quintile).…”
Section: Fetal Growth: Birth Weight and Ponderal Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exactly mechanisms of abnormal glucose metabolism in patients with first-episode psychosis are unknown. Studies suggested that inflammation, genetic polymorphisms, and chronic stress can lead to glucose metabolism abnormalities in patients with first episode psychosis (Amare et al 2017, Belvederi Murri et al 2016, Kucukgoncu et al 2019). Recent study showed that familial abnormal glucose metabolism or primary insulin signaling pathway abnormality is related to risk for psychosis (Chouinard et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mood disorders (MD) have a bidirectional association with metabolic diseases . Accumulating cross‐sectional and prospective evidence has indicated that major depressive disorder (MDD) and bipolar disorder (BD) are associated with obesity, type 2 diabetes mellitus (T2DM) and metabolic syndrome, mostly independent of lifestyle (eg, smoking, sedentary behavior, and unhealthy diet) and treatment factors (eg, use of psychotropic medications) . This collection of observations indicates that there is a mechanistic connection between MD and metabolic conditions, which is supported by converging genetic studies, reporting extensive genetic pleiotropy .…”
Section: Introductionmentioning
confidence: 99%